Identification of Worm Medication Materials in Luhu Village (Strategy Towards Stunting Elimination with Local Wisdom Approach) - Afriyanti, Sarah; Pinoa, Wiclif Sephnath (GEOFORUM, 2024)
This research was motivated by the high stunting rate in Luhu Village, Maluku, which was triggered by intestinal worm infections due to low access to modern worm medicines. This condition encourages the importance of identifying alternative deworming from local natural ingredients as an effort to eliminate stunting through local wisdom. The purpose of this study is to find and analyze the potential of natural ingredients in Luhu Village that function as deworming drugs, as well as evaluate their effectiveness in reducing worm infections in children. The method used is qualitative research with an ethnobotanical approach, where data is collected through interviews with traditional medicine practitioners, participatory observation, and laboratory tests on local plant samples. The results of the study showed that these ingredients have significant antihelmintic activity, proven through laboratory tests that support their use as an effective traditional medicine. In conclusion, local natural ingredients can be a safe and effective treatment alternative to reduce worm infections, and have the potential to contribute to stunting elimination efforts in the village. The contribution of this research is to enrich health strategies based on local wisdom, reduce dependence on modern medicine, and support the sustainability of traditional medicine in remote areas.